Coronary sinus pH during percutaneous transluminal coronary angioplasty: early development of acidosis during myocardial ischaemia in man. Issue 2 (August 1987) - Crake, T; Crean, P A; Shapiro, L M; Rickards, A F; Poole-Wilson, P A
Abstract : Coronary sinus pH was measured continuously in eight patients undergoing angioplasty to the left anterior descending coronary artery. A catheter tip pH sensitive electrode with a response time of less than 300 ms and an output of greater than or equal to 57 mV/pH unit was placed high in the coronary sinus. Recordings were obtained during a total of 24 balloon occlusions of the left anterior descending coronary artery varying in duration from 5 to 45 s. Continuous 12 lead surface electrocardiograms were recorded. During or after balloon inflation of greater than or equal to 12 s (n = 4) there was no change in coronary sinus pH or the electrocardiogram. During balloon inflation of greater than or equal to 15 s (n = 20) coronary sinus pH was unaltered but between 4 and 6 s after balloon deflation coronary sinus pH fell transiently by between 0.010 and 0.120 pH units before returning to the control value within 65 s. Ischaemic changes were seen on the electrocardiogram during 15 balloon occlusions. In individual patients the peak fall in coronary sinus pH was related to the duration of occlusion of the left anterior descending coronary artery. A rise in coronary sinus pH (alkalosis) was never seen. In man acidosis occurs in the myocardium after short periods (greater than or equal to 12 s) of ischaemia. The fall of pH precedes ischaemic changes on the surface electrocardiogram and occurs concurrently with the earliest reported changes in contractile function.